O contramovimento pela despublicização : o Escola sem Partido e os impactos da nova direita sobre a política pública de educação - Marcos Paulo Dias Leite Resende (2022)
The Brazilian political scenario, as well as the global one, has witnessed in the last decade a series of setbacks in public policies that guarantee civil and social rights, especially with the dismantling of the Welfare State. At the forefront of this process is the rise of “new right” counter-movements, a neoliberals and neoconservatives’ programmatic union against progressive policies defended by center-left coalitions. Based on this debate, this PhD Dissertation analyzes the role of the Escola sem Partido (ESP) counter-movement in what is called here the “depublicization” of Brazilian educational policy, that is, the continuous suppression of policies that promote public interests in favor of private interests related to a part of the society that defends traditional/conservative and market values. This objective unfolds in two major efforts: 1) the one that identifies and understands ESP's speeches and strategies of action in multiple areas (online and offline), defining it as a de-publicizing countermovement; and 2) the one that analyzes the effects of its actions on Brazilian educational policy, considering the time frame since its foundation, in 2004. To this end, were used methodological resources capable of mapping a) the networks that make up the coalition supporting ESP, b) its main characteristics and actions in online social networks, c) the development of the debate in Parliament and in the Executive and Judiciary d) the transformations that have taken place in educational policy over the years. Were used mainly Social Network Analysis and Quantitative and Qualitative Discourse Analysis. When analyzing the impacts of the actions of ESP and its allies, a dense network of actors that has been strengthened was identified, especially after the PT (Workers’ Party) government crisis, deepened in 2013 and evolved into Dilma Rousseff’s impeachment in 2016. Combined with the new right’s governments’ ascension to the power, the de-publicizing matters gained prominence, culminating above all in the dismantling of social rights of minorities defense policies, of inclusion and participation policies. Besides that, there was a process of resurgence of budgetary and public management policies that reduced the State's capacity in favor of benefiting the interests of the market.